Miomatosis uterina en embarazo de 37 semanas - Méndez Antamba, Estefanía Lizeth (2019)
Uterine fibroids, called benign tumors, are caused by excessive stimulation of estrogen receptors, which are a type of hormone produced by different parts of the body, acting on one or multiple cells of the uterine smooth muscle fibers, so This type of stimulation leads to excessive proliferation and the formation of these tumors, representing up to 95% of benign tumors of the female reproductive system, affecting one in four women of reproductive age. 1% to 4% of pregnancies are exposed to the appearance of uterine fibroids of which 80% of cases remain the same size. Among the risk factors that compromise the formation of uterine fibroids we have obesity, parity, family history, age among others. For the diagnosis of this pathology the physical examination, ultrasound are essential methods to properly confirm the fibroids helping us to determine their location, size and number. The early diagnosis of uterine fibroids is of great importance especially in pregnant women since some pregnancies may occur without major difficulty but a percentage of these may have certain abnormalities such as hemorrhages, threat of abortion, preterm birth, intrauterine fetal growth restriction and other fetal abnormalities. Commonly in pregnancy the behavior must be expectant, it will depend on the type of myoma and the symptoms that the patient presents, it should be kept under observation, more gynecological control to take appropriate measures.